Juridical Analysis of Primary Clinic Permits As Aesthetic Clinics - Susanti, Yulia; Khairani, Khairani; Syofyan, Syofirman; Yuniarti, Elsa (Institute Of computer Science (IOCS), 2024)
The increasing public need for health services in the field of medical aesthetics has led to an increase in the number of aesthetic clinics in Indonesia. The types of aesthetic clinics encountered in licensing can be in the form of primary clinics and primary clinics. Primary care clinics that offer basic health services are operated by doctors, but additional expertise in medical aesthetics for doctors has not been recognized by the government. This study uses a normative legal research method to find out the extent of legal provisions regarding the licensing of primary clinics that operate as aesthetic clinics. This research is expected to be useful for the government, aesthetic primary clinic operators and the community in explaining how the legal aspects of licensing primary clinics as aesthetic clinics